UMP collaborates with 8 industry partners - Mimi Rabita, Abdul Wahit (2023)
PEKAN, 9 December 2022 - Universiti Malaysia Pahang (UMP) entered into a joint agreement with eight industries in developing research and work-based learning (WBL) which would benefit in producing holistic graduates.